Work disability among two cohorts of women with recent onset rheumatoid arthritis: A survival analysis - PhD, S. Reisine (2007)
OBJECTIVE: To analyze factors associated with leaving employment among women with newly diagnosed rheumatoid arthritis (RA) in two patient cohorts. METHODS: Women with RA were recruited from a national sample of rheumatologists in 1987 and 1998. Patients had to be diagnosed with RA for less than 18 months, 18 yrs and older, have no other disabling health condition. 48 and 91 women were in the 1987 and 1998 cohorts, respectively. Data were collected by phone for 4 yrs. Survival analysis was conducted using Kaplan-Meier curves and a proportional hazards generalized linear model to assess whether the time to stopping work differed between the cohorts and to identify baseline predictors and time-varying covariates of leaving work. RESULTS: Most patients were <50 years, married, >12 years education, white. Fifteen patients (31%) in the 1987 and 24 pts (26%) in the 1998 cohort stopped working in the observation periods. Kaplan-Meier survival curves for each cohort were not significantly different. Multivariate analyses showed women in 1998 cohort were significantly more likely to stop working compared to the earlier cohort (p=0.03) as were married women (p=0.03), those with more joint deformities (p=0.00) and more disease flares (p=0.00). A significant flares by cohort interaction (p=0.01) showed that for the 1987 cohort, those with one or more disease flares had the greatest risk of stopping work. CONCLUSION: Unexpectedly, the cumulative rate of stopping work among women in the 1998 study did not differ from that among women diagnosed more than 16 years ago. However, disease flares greatly affected employment in the 1987 but not the 1998 cohort which may indicate that newer medications are effective in maintaining functional status among those with more severe disease activity, measured by number of flares, in the 1998 group.